Respuestas
Respuesta dada por:
25
La expresión es:
![2as=v_{f}^{2}-v_{o}^{2} 2as=v_{f}^{2}-v_{o}^{2}](https://tex.z-dn.net/?f=+2as%3Dv_%7Bf%7D%5E%7B2%7D-v_%7Bo%7D%5E%7B2%7D)
Luegó despejando a se.tiene:
![a=\frac{v_{f}^{2}-v_{o}^{2}}{2s} a=\frac{v_{f}^{2}-v_{o}^{2}}{2s}](https://tex.z-dn.net/?f=a%3D%5Cfrac%7Bv_%7Bf%7D%5E%7B2%7D-v_%7Bo%7D%5E%7B2%7D%7D%7B2s%7D)
Despejando s:
![s=\frac{v_{f}^{2}-v_{o}^{2}}{2a} s=\frac{v_{f}^{2}-v_{o}^{2}}{2a}](https://tex.z-dn.net/?f=+s%3D%5Cfrac%7Bv_%7Bf%7D%5E%7B2%7D-v_%7Bo%7D%5E%7B2%7D%7D%7B2a%7D)
Despejando
![v_{f}^{2}=2as+v_{o}^{2}\\<br />v_{f}=\sqrt{2as+v_{o}^{2}} v_{f}^{2}=2as+v_{o}^{2}\\<br />v_{f}=\sqrt{2as+v_{o}^{2}}](https://tex.z-dn.net/?f=+v_%7Bf%7D%5E%7B2%7D%3D2as%2Bv_%7Bo%7D%5E%7B2%7D%5C%5C%3Cbr+%2F%3Ev_%7Bf%7D%3D%5Csqrt%7B2as%2Bv_%7Bo%7D%5E%7B2%7D%7D)
Despejando
se tiene:
![2as-v_{f}^{2}=v_{o}^{2}\\v_{o}^{2}=2as-v_{f}^{2}\\<br />v_{o}=\sqrt{2as-v_{f}^{2}} 2as-v_{f}^{2}=v_{o}^{2}\\v_{o}^{2}=2as-v_{f}^{2}\\<br />v_{o}=\sqrt{2as-v_{f}^{2}}](https://tex.z-dn.net/?f=2as-v_%7Bf%7D%5E%7B2%7D%3Dv_%7Bo%7D%5E%7B2%7D%5C%5Cv_%7Bo%7D%5E%7B2%7D%3D2as-v_%7Bf%7D%5E%7B2%7D%5C%5C%3Cbr+%2F%3Ev_%7Bo%7D%3D%5Csqrt%7B2as-v_%7Bf%7D%5E%7B2%7D%7D)
Saludos
Luegó despejando a se.tiene:
Despejando s:
Despejando
Despejando
Saludos
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años